Flexible eddy current array measurement system for crack detection in weld zones of steel structures - Le Quang Trung; Nguyen Duc Khuong; Tran Thi Hoai Dung; Naoya Kasai; Tran Mach Tuan Kiet; Kouichi Sekino; Honoka Fukuda (Communications Engineering)
Abstract Crack detection in weld zones of steel structures is essential for ensuring structural safety and reliability. Eddy current (EC) testing is widely used due to its non-contact nature and high sensitivity to surface and sub-surface cracks. This study reports a flexible eddy current array (FECA) sensor with six bendable channels designed to detect surface and sub-surface cracks in the weld zones of steel structures. The excitation coils are connected in series to enhance signal intensity, while interleaved detection coils minimize lift-off effects and improve sensitivity. A real-time measurement system was developed by integrating the FECA sensor with a LabVIEW-based digital lock-in amplifier. Experiments using 500 kHz and 5 kHz excitation frequencies demonstrated effective detection of surface and sub-surface cracks, respectively, including under zinc coatings. Despite manual scanning, stable and repeatable signals were recorded across multiple channels. The proposed system offers high sensitivity, real-time capability, and adaptability to complex geometries.